The dinamics of water quality on tiger shrimp (Penaeus monodon) cultivation using probiotic in semi intensive pond - Sahrijanna, Andi; Suwoyo, Hidayat Suryanto; Tahe, Suwardi; Sahabuddin, Sahabuddin (International Journal of Environment, Agriculture and Biotechnology, 2020)
Tiger shrimp (Penaeus monodon) is one of the aquaculture commodities which is still be Indonesia leading export commodity. However, since the outbreak of white spot syndrome virus (WSSV), tiger shrimp cultivation began to leave by farmers and switch to vannameiwhich is more profitable and more resistant to disease. This condition should be avoided considering tiger shrimp are native shrimp of Indonesia whose market demand is still quite high. Therefore, some efforts to improve tiger shrimp cultivation is necessary. One of the efforts to improve tiger shrimp cultivation is by improving culture medium in pond using RICA probiotics. The study was conducted on experimental pond installation in Takalar regency. The treatments were: A) liquid RICA probiotics, B) powdered RICA probiotics. Data of water quality i.e: phosphate, nitrate, nitrite, organic matter, ammonia, TSS,alkalinity and temperature, salinity, DO, pH were analyzed descriptively. The results of the study showed that the use of liquid RICA probiotics had average of phosphate 0.3531 mg/L, nitrate 0.2164 mg/L, nitrite 0.0090 mg/L and pH 8.11 whereas by using powdered RICA probiotics the average phosphate was 0.1851 mg/L, nitrate 0.0573 mg/L, nitrite 0.0069 mg/L and pH 8.51. Application of liquid and powdered probiotics in semi-intensive tiger shrimp could effectively maintain water quality parameters like NH3-N, NO2-N, NO3-N and total organic matter